At the crossroads of tradition and modernity: raphael and the cultural politics of popular music in Spain. (1st April 2013) - Wheeler, Duncan
In the first academic article on Raphael, I attempt to counteract the Anglo-centric bias still prominent in much popular music studies by focusing on one of Spain's most commercially successful music stars whose recording and touring career is now in its sixth decade. I begin by examining how, in both musical and celebrity terms, Raphael came to simultaneously embody tradition and modernity in 1960s Spain. Then, in the second part, I explore his durability as a global superstar and locate his music and performance style within broader national and international trends. This analysis is deployed to sketch an objective aesthetic and culturally sensitive response to a very subjective question: does Raphael warrant the veneration and/or contempt in which he has often been held?